Reading motivation scale for texts: A validity and reliability study [Metinlere yönelik okuma motivasyonu ölçeǧi: Geçerlik ve güvenirlik çalışması] - (:unkn) unknown (Ankara University, 2013)
In this study, it was aimed to develop a reading motivation scale in order to determine reading motivations of students for texts. The work group was consisted of 259 students who were attending to 5th grade of the schools in the center of Sakarya during the 2nd term of 2010-2011 school year. First of all, in the process of developing the scale, a review of literature was made and a pool of 60 items was created. Opinions of experts were applied for the content validity and exploratory factor analysis was conducted for the construct validity of the scale. Finally, internal consistency coefficient was applied for the reliability studies. When the results were assessed, a valid and reliable scale that consists of 22 items and four factors which are "perceived reading difficulty," "reading ability," "effort/being appreciated to read" and "social aspect of reading" was obtained. The four factors found in the scale explained %46.23 of the total variance. In total, internal consistency coefficient was found as.81. These values show that the scale explained the reading motivations of the primary school students of the 5th grade for texts in a valid and reliable manner.
Keywords: Reading; Reading motivation; Reliability; Scale development; Text; Validity